Soutenabilité de l’arganeraie marocaine. - Hassan Faouzi; Julie Martin (Confins)
Sustainability of the Moroccan arganeraie. Between valuation of argan oil and non-regeneration of the argan tree. Argane oil production is the most famous of the argan tree. In the 1990s, with the various discoveries of its culinary, cosmetic and medicinal, it has been a renewed interest. It is one of local resources in the South which has been in recent years, most commercial climbing dramatically. But in the southwest of Morocco Argan stands are steadily decreasing and regeneration is compromised. Depending on the environment of national and international development, conservation of the argan tree is the result of the economic exploitation of its resources. Argan oil is definitely on that production can rest a draft socio-economic development. Building on its success in a decade, argan oil has flooded the market of cosmetics in Europe and elsewhere. However, a few years later, we are forced to conclude that the commercial development of the industry "argan oil" had no real effect on the conservation of the arganeraie; it goes in the opposite direction of the objectives of developers.